Adaptive multiphoton and harmonic generation microscopy for developmental biology - Thayil, A; Jesacher, A; Watanabe, T; Wilson, T; Srinivas, S; Booth, M (2010)
Specimen-induced aberrations often affect microscopes, particularly when high numerical aperture lenses are used to image deep into biological specimens. These aberrations cause a reduction in resolution and focal intensity. This is particularly problematic in multiphoton microscopy, where the non-linear nature of the signal generation process means that the signal level is strongly affected by changes in the focal spot intensity. We have applied the techniques of adaptive optics to correct aberrations in two-photon fluorescence and harmonic generation microscopes, restoring image quality. In particular we have used these microscopes for studies in developmental biology and for the imaging of mammalian embryos. © 2010 Copyright SPIE - The International Society for Optical Engineering.